"As Good as Money in the Bank": Building a Personal Safety Net with the Earned Income Tax Credit. (13th March 2018) - Tach, Laura; Halpern-Meekin, Sarah; Edin, Kathryn; Amorim, Mariana
Abstract: The public safety net has increasingly functioned as a system that rewards work, but many low-wage workers now face a double bind: unstable incomes and volatile expenses. We ask how low-wage workers make resource allocation decisions under conditions of uncertainty by examining how they spend and save their tax refunds. Using data from in-depth interviews with a sample of 115 lower-income working families, we find that more than three quarters of families experienced an income or expense shock in the past three years. Although many had aspirations for upward mobility, the insecurity of daily life meant they devoted most of their refund dollars to creating a personal safety net to cushion against income and expense shocks. What appeared to be distinct types of allocations often had the same underlying rationale goal of improving a family's economic security in the near term. By saving, purchasing durable goods, stockpiling household staples, and paying off debts to kin and creditors at tax refund time, families leveraged their tax refund dollars into multiple forms of self-insurance. Respondents held aspirations for upward mobility that correspond strongly with those of middle-class Americans, but they did not feel they had the luxury of setting aside resources for long-term mobility goals given the instability and insecurity of their work and family lives. Instead, they invested their refunds in more precautionary ways. What might be viewed as current consumption by outsiders was actually a form of in-kind investment that occurred outside the purview of the formal banking system.